Comprehensive Clinico-Demographic Analysis Of Malignant Pleural Effusions In The Bulgarian Population: Insights From An Observational Case-Control Study - Aleksiev V.; Yavorov B.; Markov D. (Acta Medica Bulgarica)
Malignant pleural effusions represent a significant problem both from a clinical perspective and from a socioeconomic standpoint. They constitute a substantial burden on the healthcare system. Affecting approximately 1 million people each year, malignant pleural effusions are a leading cause of debilitating dyspnea and decreased quality of life for many patients. Distant metastasis to the pleural layers is one of the most common complications in many malignancies, with approximately 20% of cancer patients experiencing pleural effusions during treatment. The average survival after diagnosis varies between 4 and 9 months, depending on the type and stage of neoplasm. This underscores the necessity for proper understanding of this pathology and the development of an appropriate diagnostic and therapeutic algorithm to address its consequences. To clarify the clinico-demographic aspects of malignant pleural effusions, we carried out a one-year case-control observational study, which included patients of varying ages, clinical manifestations and primary etiologies. A total of 151 patients were included in the analysis. The control group consisted of 72 patients, all of whom were diagnosed with benign disease, confirmed by subsequent biopsy. Of these, 38 cases were confirmed as inflammatory, and 34 were verified as pleural effusions of non-inflammatory origin. Malignant pleural involvement was confirmed in 79 patients. These two groups are representative of the main types of pleural pathology. We aimed to define the main characteristics of pleural malignancies and correctly recognize patients at risk.